The Role of Social Support in Dealing With the Different Types of Stressors: Social Support in the Workplace - Leow, Kenneth; Leow, Serena Wai Yee * (IGI Global, 2022)
Social support plays an integral role in every person’s mental health and well-being. This is especially apparent in the work environment, where stress levels can range from moderate to severe depending on how each individual manages and cope with his or her own circumstances. The goal in this chapter is to outline current research on the role of social support in dealing with different types of stressors in the workplace. Further, this chapter will summarize key findings and concepts, particularly focusing on the following areas: 1) definition of social support, 2) social support theories, 3) social support on mental health and well-being, and 4) social support as a form of intervention in the workplace.